Analisis Kemampuan Pemahaman Konsep Bangun Ruang Sisi Datar Ditinjau Dari Gaya Kognitif Field Independent dan Field Dependent - Kurnia, Siti Sarah; Prayitno, Sudi; Junaidi, Junaidi (Griya Journal of Mathematics Education and Application, 2025)
This study aims to describe students' conceptual understanding abilities in polyhedron spatial geometry material in terms of their cognitive style. The type of research used is descriptive qualitative. The subjects of the study were 4 students of class IX-G of SMP Negeri 5 Mataram in the 2024/2025 academic year, consisting of 2 students with the field independent cognitive style category and 2 students with the field dependent cognitive style category. The data collection techniques used were tests and interviews. Data analysis techniques with data reduction, data presentation, and draw a conclusion. The results of this study indicate that (1) the conceptual understanding ability with the field independent cognitive style is very good, both subjects can meet all indicators of conceptual understanding, namely being able to restate concepts, being able to classify objects based on concepts, being able to provide examples and non-examples of concepts, and being able to present concepts in the form of mathematical representations. (2) the conceptual understanding ability with the field dependent cognitive style is still lacking, both subjects have not been able to meet all indicators of conceptual understanding, subjects can only meet 3 indicators of conceptual understanding used.